Rol educativo de enfermería y su incidencia en la prevención de infecciones de vías urinarias en adolescentes embarazadas en Centro de Salud Trinitaria, octubre 2018 – abril 2019 - Echeverría Castro, María Isabel (2019)
Urinary tract infections or also called urinary tract infections are very common conditions in people especially in pregnant women, where they have taken a high prevalence, which are acquired either by carelessness of the individual or by ignorance of the subject . Currently teens in pregnancy are the most vulnerable group to have urinary tract infections since the body goes through major changes, physical, hormonal which generates an alteration in the urinary system as the new being is taking place. Faced with this situation, health personnel have the responsibility, together with the patient, to ensure their health, and this is where the educational role of nursing plays a fundamental role in providing adequate and timely information on the subject. In the next project, the main objective will be the application of the nursing educational role for the prevention of diseases which will be carried out in the Trinitarian Health Center where non-experimental inductive-deductive methods will be used, resulting in the educational role of Nursing fulfills important functions for what is recommended will be in constant learning to share with citizens.